Citizen Perceptions of Green Space Park in Pokhara, Nepal - Parajuli, Biswo Kallyan; Giri, Padam; Shrestha, Krishna Mohan; Suvedi, Murari (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Pokhara valley is located in western Nepal at an elevation of about 3,000 feet above sea level. It was declared a municipality in 1959 with an estimated population of 4,000. Since then, the city of Pokhara has faced tremendous growth pressure. Its population reached 200,000 in 2005 - a 50-fold increase in population in 46 years. Land prices have increased at a much higher rate than the population. Most of the arable land has been replaced by roads and buildings. There is a concern that Pokhara is facing growth pressure similar to that of Kathmandu Valley, as described by Pradhan and Perera (2005). As land prices soar, there is tremendous pressure on public land for development, and the municipality has not been able to maintain open space for public use. Pokhara has established few sites as public parks, and most of these parks are small parcels of land fenced for protection from cattle and water buffalo with few or no plants/ flowers and other resources for leisure time activities. There are no plans for the development of a nature park or a green space area where people could see, feel and touch ornamental plants and flowers. Furthermore, the city lacks an open green space where people could walk, jog or spend leisure or free time. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1494 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p. 34-45